Rapid Adjustment of Circadian Clocks to Simulated Travel to Time Zones across the Globe. (December 2015) - Harrison, Elizabeth M.; Gorman, Michael R.
Daily rhythms in mammalian physiology and behavior are generated by a central pacemaker located in the hypothalamic suprachiasmatic nuclei (SCN), the timing of which is set by light from the environment. When the ambient light-dark cycle is shifted, as occurs with travel across time zones, the SCN and its output rhythms must reset or re-entrain their phases to match the new schedule—a sluggish process requiring about 1 day per hour shift. Using a global assay of circadian resetting to 6 equidistant time-zone meridians, we document this characteristically slow and distance-dependent resetting of Syrian hamsters under typical laboratory lighting conditions, which mimic summer day lengths. The circadian pacemaker, however, is additionally entrainable with respect to its waveform (i.e., the shape of the 24-h oscillation) allowing for tracking of seasonally varying day lengths. We here demonstrate an unprecedented, light exposure–based acceleration in phase resetting following 2 manipulations of circadian waveform. Adaptation of circadian waveforms to long winter nights (8 h light, 16 h dark) doubled the shift response in the first 3 days after the shift. Moreover, a bifurcated waveform induced by exposure to a novel 24-h light-dark-light-dark cycle permitted nearly instant resetting to phase shifts from 4 to 12 h in magnitude, representing a 71% reduction in the mismatch between the activity rhythm and the new photocycle. Thus, a marked enhancement of phase shifting can be induced via nonpharmacological, noninvasive manipulation of the circadian pacemaker waveform in a model species for mammalian circadian rhythmicity. Given the evidence of conserved flexibility in the human pacemaker waveform, these findings raise the promise of flexible resetting applicable to circadian disruption in shift workers, frequent time-zone travelers, and any individual forced to adjust to challenging schedules.